Relação atributo funcional-ambiente na assembleia de peixes de um rio intermitente da região Semiárida do Brasil - Almeida, José Robério de Sousa (2020)
One of the great challenges of Ecology is to understand which processes define the patterns of diversity, especially among local communities. In semi-arid areas with well-marked wet and dry seasons, fish communities experience successive contractions/habitat expansions. These events directly influence the longitudinal continuum of the river, selecting species with characteristics that favor their survival in these conditions. Based on this premise, this study evaluated the potential environmental filtration in the functional structuring of the fish assembly of a river in the semi-arid region of Brazil during 2013, when the drought period was more prolonged. The Apodi/Mossoró River is originally intermittent with a magnitude of inundation defined by the volume of rainfall. Its natural flow was altered by the construction of 618 dams, with a capacity of 4.7 million m³, for irrigation and water supply purposes. Thus, to test the hypothesis “the relationship between functional attributes and environmental conditions is similar in the periods of drought and rain in the fish assembly of the Apodi River”, we evaluated the attribute-environment relationship in the dry and rainy seasons. For this, ecomorphological measures of all species of fish collected were obtained and bibliographic bases were consulted to compose a matrix of functional attributes related to habitat use, locomotion, feeding and reproduction. Subsequently, to test the response of the functional characteristics of the fish assemblage to environmental conditions in the dry and wet seasons, an RLQ ordering analysis was used. To assess the statistical significance of the relationship between functional attributes and environment, permutations were performed with two null models and a fourth-corner analysis that evaluated individual associations between attributes and environment. In total, 21 species of fish were recorded, six environmental variables and 18 functional attributes were evaluated. The fish assemblages presented a random distribution, indicating that there was no dependence on environmental characteristics (model 2, p = 0.31). We did not register a significant relationship between functional attributes and environmental variables (model 4, p = 0.44). However, we identified three significant positive associations (p <0.05) between attributes and environmental variables: the Pectoral fin position (PFps) attribute with channel width, Pectoral fin configuration ratio (FPar) with temperature and Surface ratio fins and body size (Fsf) with depth. No differences were found between the rainy and dry season assemblies, suggesting that rivers in the Brazilian semiarid in the context of low rainfall do not corroborate the premise of the Habitat Template Theory (HTT, TOOWSEND & HILDREW, 1994)